Design and Build a Website-Based Teacher Payroll Processing Information System at SMKTIK Yadika Cicalengka - Nova Indrayana Yusman; Achmad Taufiq Kartaatmadja; Dimas Aprizon (International Journal of Ethno-Sciences and Education Research, 2023)
The design of this teacher payroll processing information system was developed to make it easier to manage teacher salaries at SMKTIK Yadika Cicalengka so as to minimize duplication.for the system design using the OOAD (object Oriented Analysis and Design) while the model used is RUP (Rational Unified Process) where the development tools are UML (Unified Modeling Language) There is also an explanation of the information system design process. Website-based payroll processing that will be built, starting from the design of use case diagrams, activity diagrams, sequence diagrams, class diagrams, user interfaces, hardware design and in designing this hardware requires hardware configuration, hardware specifications, and software specifications